Аналоги просторів типу S частково парних функцій - Літовченко, В.А. (Український математичний журнал, 2013)
Построены аналоги пространств типа S, элементы которых являются четными функциями относительно части компонент своих аргументов. Получена формула представления степени оператора Бесселя через соответствующие степени дифференциального оператора, позволяющая установить связь между этими пространствами в терминах преобразования Фурье – Бесселя и выяснить некоторые основные свойства типовых операций над их элементами. We construct analogs of S-type spaces whose elements are functions even in certain parts of components of their arguments. We deduce a formula expressing the power of a Bessel operator via the corresponding powers of differential operators. The proposed formula enables us to establish the relationship between these spaces in terms of the Fourier–Bessel transformation and to clarify some basic properties of typical operations over their elements.